Learning Innovation through BigBlueButton technological tool implementation in statistics courses at UNED, Costa Rica - Sánchez Godínez, Elisa; Stradi Granados, Stella (Innovaciones Educativas, 2020)
In distance learning, synchronous and asynchronous communication tools support higher education students’ teaching-learning processes in all different majors in formal and informal programs. As an example of the use given to information and communication technologies at Universidad Estatal a Distancia (UNED), BigBlueButton was employed to offer virtual tutoring in some of the courses, among other purposes. The research focuses on the students’ perceptions regarding the tool’s use and usefulness. For that purpose, a sample of 69 students enrolled in two courses of the Diploma in Business Administration answered a questionnaire. The results indicate that the BigBlueButton tool happens to be an effective option for training students since it meets the purposes of face-to-face tutoring and allows students to obtain savings in time and money by not having to commute to the university. The tool facilitates the interaction between the students and their tutors. It is also possible to access the recorded sessions, and it helps understanding content while offering immediate doubt clarification